2015
DOI: 10.1039/c5cp04608d
|View full text |Cite
|
Sign up to set email alerts
|

Absolute configuration and chiral self-assembly of rubrene on Bi(111)

Abstract: We investigated the chiral self-assembly of rubrene molecules on a semi-metallic Bi(111) surface using low-temperature scanning tunneling microscopy. The absolute configuration of isolated rubrene enantiomers was identified from high-resolution images. Two types of homochiral domains of rubrene monomers and hexamers were observed, respectively. For rubrene monomers, chiral separation was spontaneous with each chiral monomer appearing in their respective domain. For rubrene hexamers, two levels of organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
2
7
0
1
Order By: Relevance
“…Inside the row, pairs of β-molecules orient the upward tilted part of their tetracene backbone towards each other. The coexistence of different C 42 H 28 configurations was previously reported for a variety of surfaces [25,35,36] and is not specific to graphene.…”
Section: Graphene-c 42 H 28supporting
confidence: 55%
See 2 more Smart Citations
“…Inside the row, pairs of β-molecules orient the upward tilted part of their tetracene backbone towards each other. The coexistence of different C 42 H 28 configurations was previously reported for a variety of surfaces [25,35,36] and is not specific to graphene.…”
Section: Graphene-c 42 H 28supporting
confidence: 55%
“…In that work a multilayer C 42 H 28 film was deposited at room temperature and subsequently annealed to achieve a monolayer coverage. Different superstructures of C 42 H 28 with twisted and tilted backbones were presented in [ 25 27 34 ] for Au(111) and in [ 35 ] for Bi(111). In these reports, the deposition of molecules was performed at 5 K [ 25 27 34 ] and 100 K [ 35 ] with subsequent annealing at room temperature [ 25 27 34 ] and 350 K [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…31 However, few reports address the superstructure of C 60 molecules adsorbed on semi-metal substrates. It is found that thin lms of organic molecules grown on a semi-metallic Bi(111) surface shows a lot of interesting phenomena, such as the ordered crystalline layer with the standing-up orientation of pentacene molecules, 32 the chiral self-assembly of rubrene molecules, 33 structural transitions in different monolayers of cobalt phthalocyanine lms, 34 and the Moire' pattern in C 60 thin lms. 35 In this study, we use Bi(111) as the substrate and studied the structure transition of the C 60 monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…2010年, Huang等 人 [29] 用化学反应法得到红荧烯晶体, 采用单晶X射线 衍射证明两种晶体分别是单斜晶体和三斜晶体. 在 2014年, Obata等人 [33] [1,16] . 因此, 在 中可以看到并四苯几乎垂直于基底 [34,35] .…”
unclassified